2022
DOI: 10.3390/ijms23137220
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Utilization Promotes Systemic Infection of Salmonella Typhimurium in Mice

Abstract: Salmonella Typhimurium is an invasive enteric pathogen that causes gastroenteritis in humans and life-threatening systemic infections in mice. During infection of the intestine, S. Typhimurium can exploit nitrate as an electron acceptor to enhance its growth. However, the roles of nitrate on S. Typhimurium systemic infection are unknown. In this study, nitrate levels were found to be significantly increased in the liver and spleen of mice systemically infected by S. Typhimurium. Mutations in genes encoding nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Wanwu Li et al. reported the mechanism of cytoplasmic acidification through transport and use of nitrate in Salmonella typhimurium, which ultimately promotes the intracellular replication and systemic infection of Salmonella Typhimurium ( Li et al., 2022 ). In this study, we found that LF82 infection resulted in macrophages acidifying rapidly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wanwu Li et al. reported the mechanism of cytoplasmic acidification through transport and use of nitrate in Salmonella typhimurium, which ultimately promotes the intracellular replication and systemic infection of Salmonella Typhimurium ( Li et al., 2022 ). In this study, we found that LF82 infection resulted in macrophages acidifying rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen metabolism is one of the important mechanisms for bacteria to adapt to an intracellular acid environment. Nitrate utilization, which is activated by both the global regulator Fnr and the nitrate-sensing two-component system NarX/NarL in S. Typhimurium, promotes S. Typhimurium intracellular replication and systemic pathogenicity ( Li et al., 2022 ). In this study, we found that nitrogen-metabolism-related genes of LF82 were upregulated in acid conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ∆phoBR and ∆msbB mutant strains were constructed using the λ-Red recombinase system by replacing the target genes with a chloramphenicol or kanamycin resistance gene cassette, respectively, as described previously [50]. The S. Typhimurium WT and ∆msbB, which express green fluorescent protein (GFP), were constructed through electrotransformation, as described previously [51]. S. Typhimurium was cultured in Luria-Bertani (LB) medium at 37 • C to the stationary phase (OD 600 = 1.0, ~10 9 CFUs/mL).…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…Li et al observed an increased nitrate level during the systemic infection of STM in mice. Nitrate utilization was shown to enhance its replication inside macrophages as it acidifies the cytoplasm of STM followed by activation of SPI-2 genes [18]. Nevertheless, the NarL regulon has been more extensively studied in Escherichia coli [19,20], but hardly in STM.…”
Section: Introductionmentioning
confidence: 99%